The race of the century : the battle to break the four-minute mile - Bascomb, Neal (Scholastic Focus, 2022)
Chronicles the efforts of English Roger Bannister, Australian John Landy, and American Wes Santee to be the first man to run a four-minute mile, and explores the beliefs about running, exercise, and the amateur athlete at the time. Includes black-and-white photographs.